DETERMINATION OF CONTACT PRESSURE IN CYLINDRICAL DIRECTIONAL WITH AXIS MISALIGNMENT - VICHAVKA, ANATOLII; DYKHA, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The basis of the solution of the problems of skewness in the sliding resistance is the assumption that each cross-section is in a state of plane deformation according to the stiffness of the characteristics, and the continuity of the functions of the transition from the cross-section to the cross-section is ensured by the geometric continuity of the shaft and bushing along the axis of the cylinders. The exact analytical solution to the problem of contact of elastic cylinders with a skew of finite dimensions in a spatial formulation is unknown. Almost all known solutions are approximate and are based on reducing the spatial problem to a set of plane deformations related by the condition of commonality of the layer deformations with the shaft deformations. The influence of the guide dimensions and the skew angle on the magnitude of the maximum contact pressures in a cylindrical sliding guide is determined. The calculation scheme of contact with skew of a cylindrical guide is presented. To solve the contact problem, the following system of initial equations is used: the condition of equilibrium in contact, the condition of continuity in contact, the geometric condition and the dependence for contact pressure. As a result of solving the system, we obtain an integral equation for the contact angle and contact pressure in any section of the guide. The integral in the general solution is reduced to elementary functions with the results given in the table. For the function of displacements in the form of a trapezoid at a given skew angle and length of the contact line, graphs of determination of displacements in contact and, accordingly, contact pressure are given. The value of contact pressure is decisive for calculating the wear of the guide along the length with skew of the axes.